Experience Affects EEG Event-Related Synchronization in Dancers and Non-dancers While Listening to Preferred Music - Nakano, Hiroko; Rosario, Mari-Anne M.; de Dios, Constanza (Frontiers in Psychology, 2021)
EEGs were measured to investigate the effect of dance expertise on listening to preferred dance music. Dancers and nondancers passively listened to instrumental music of their preferred genre (Argentine tango for dancers; classical or jazz for nondancers), alternate genres, and silence. Time-frequency analysis of 100s-long music pieces revealed that both dancers and nondancers initially showed an event-related desynchronization (ERD) in the alpha frequency band for their preferred music. However, after 40s post onset, the alpha activity associated with preferred music showed event-related synchronization (ERS) in the parieto-occipital region only in dancers. The posterior alpha ERS in dancers was maintained through the rest of music listening. The alpha ERS is hypothesized to reflect the inhibition of neuronal activity in the posterior region, thus facilitating continuous attention processes in dancers of Argentine tango. Analysis also revealed that both dancers and nondancers showed an immediate and sustained increase of gamma band activity in response to preferred music. This is consistent with theories that gamma reflects higher-level cognitive operations such as recognition of familiar music, as well as enhanced emotional arousal. Dancers showed enhanced attention and neural responsiveness to emotion, indicating a dance expertise effect.